Human Leukocyte Antigen Haplotypes in the Genetic Control of Immune Response to Measles-Mumps-Rubella Vaccine - Ovsyannikova, Inna G.; Pankratz, V. Shane; Vierkant, Robert A.; Jacobson, Robert M.; Poland, Gregory A. (The Journal of infectious diseases, 2006)
To elucidate the contribution of human leukocyte antigen (HLA) haplotypes and their genotypic combinations to immune status after measles-mumps-rubella (MMR) vaccination, 346 children 12–18 years of age were studied. The class I A*29-Cw*16-B*44 haplotype was associated with lower levels of immunoglobulin G (IgG) antibody to both measles (P=.08) and mumps (P=.03) viral antigens. The A*26-Cw*12-B*38 haplotype was associated with higher cellular immune responses to measles (P=.02) and mumps (P=.01) vaccine viruses. Subjects with the class II DRB1*03-DQB1*02-DPB1*04 haplotype had higher lymphoproliferative responses to measles virus (P=.01) and mumps virus (P=.006). The DRB1*15/16-DQB1*06-DPB1*03 haplotype was associated with high levels of IgG antibody to measles virus (P=.09) but low levels of IgG antibody to rubella virus (P=.02), whereas DRB1*04-DQB1*03-DPB1*03 was associated with high lymphoproliferative responses to both measles (P=.01) and rubella (P=.002) vaccine viruses. A*26-Cw*12-B*38 was associated with both mumps virus–specific humoral (P=.007) and cell-mediated (P=.01) immune responses after 2 doses of MMR vaccine. Haplotype DRB1*04-DQB1*03-DPB1*03 was associated with both lower rubella virus IgG antibody levels (P=.02) and higher rubella virus–specific lymphoproliferation (P=.002). Better characterization of such HLA profiles could inform and improve the design of novel epitope-rich vaccines and help to predict protective immune responses at the individual and population level